ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED, MARKET VALUE ADDED, FINANCIAL VALUE ADDED DAN REFINED ECONOMIC VALUE ADDED PADA PERUSAHAAN DI BURSA EFEK INDONESIA SEKTOR ENERGI PERIODE 2019-2023 - Rudy Syafariansyah,; Agus Riyanto,; Hendra, (OBOR: Oikonomia Borneo, 2025)
The study aims to analyze the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The evaluation was carried out using four value-added methods, namely EVA, MVA, FVA and REVA.This type of research uses descriptive quantitative, with the object of research on three coal mining sub-sector companies, namely PTBA, SMMT and TCPI. Data obtained from the company's annual financial statements over a five-year period. The results showed that each company has diverse financial performance. PT Bukit Asam Tbk shows a more stable and positive performance than the other two companies. The analysis with the four methods provides relevant information to evaluate the sustainability of value creation and strategic decision making, especially in the energy sector that faces global challenges and energy transition regulations.